1994
DOI: 10.1002/app.1994.070540709
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of polyamide 6 made by reactive extrusion. II. Analysis of microstructure

Abstract: SYNOPSISConsideration is given to the characterization of microstructure in polyamide 6 prepared by polymerization of e-caprolactam in a corotating twin-screw extruder. Results obtained by FTIR, WAXD, DSC, and DMTA are discussed in terms of the molecular mass of the polymer, the thermal history of the material. and the influence of residual monomer. I NTRO DUCT1 0 NA previous investigation considered the preparation of polyamide 6 (PA6) by the catalyzed anionic polymerization of t-caprolactam in a corotating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…There are complex interactions among such phenomena as fluid flow, heat transfer and chemical reaction during the reactive extrusion process, which cause the theoretical research to be very difficult. [1][2][3][4][5][6][7][8][9][10][11] The existing theoretical investigations have been mainly confined to one-dimensional (1D) models and have generally simplified the complicated relationships among fluid flow, chemical reaction, material structures, physicochemical properties, and heat transfer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are complex interactions among such phenomena as fluid flow, heat transfer and chemical reaction during the reactive extrusion process, which cause the theoretical research to be very difficult. [1][2][3][4][5][6][7][8][9][10][11] The existing theoretical investigations have been mainly confined to one-dimensional (1D) models and have generally simplified the complicated relationships among fluid flow, chemical reaction, material structures, physicochemical properties, and heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…The investigations into the polymerization of polyamide 6 (PA6) in extruders can date back to 1968; it was Illing who reported the method of the anionic polymerization of caprolactam into PA6 in twin screw extruders 1, 2. Since the 1980s, Menges, Michaeli, and Berghaus and their colleagues at the University of Aachen and the IKV Company,3–6 as well as Hornsby and Tung at the University of Brunel7 and White and Kye at the University of Akron,8–11 all applied themselves to the research of this process.…”
Section: Introductionmentioning
confidence: 99%
“…However, such reactions are affected not only by the type of initiation system, and active growth centers but also by the concentration of initiation system and reaction conditions which play an undeniable role in the characteristics of the final product. In other words, initiation system comprising a catalyst and an activator, and also reaction conditions have a major influence on the polymerization rate, yield, structure, and properties of the synthesized materials, which, in turn, affect the other characteristics of the final polymer [35][36][37][38][39]. The process type should also be considered carefully for the selection of a suitable initiation system [31,[35][36][37][38][39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Features of this method are the very fast polymerization process and the narrow molecular weight distribution [10]. Hornsby and Tung [11] showed that the impact strength and elongation-at-break values of Nylon 6 obtained by this method are higher than those of other commercial polyamides.…”
Section: Introductionmentioning
confidence: 99%